PENGARUH VARIASI PENGGUNAAN ABU AMPAS TEBU (AAT) DAN ABU BATU (AB) SEBAGAI BAHAN PENGGANTI SEBAGIAN SEMEN TERHADAP KUAT TEKAN MORTAR - Sati, Rara Ayu; Supriani, Fepy; Afrizal, Yuzuar (Inersia: Jurnal Teknik Sipil, 2019)
Bagasse ash and stone ash are materials that have some elements that fimilar to  cement elements. Bagasse ash is a waste that has not been utilized by community. Stone ash is a waste of stone crusher whose utilization in building structures is still lacking. This research was aimed to know compressive strength of the mortar which use bagasse ash and stone ash as a partial substitute of cement. The method of casting and compressive strength test of the mortar referred to SNI 03-6825-2002. The total of mortar cubes was 128 specimens with dimensions of 50 mm x 50 mm x 50 mm. Variations of bagasse ash and stone ash used were 5%, 10%, 15%, 20% and 25% of the weight of cement. The range of initial flow values used are 105%-115% (SNI 03-6882-2002). Mortar cubes cured for 27 days and test of mortar was conducted at 28th days. The value of mortar compressive strength variation of bagasse ash decrease from normal mortar compressive strength with a decrease respectively of 0.62%, 2.14%, 7.33%, 7.50% dan 9.53%. Compressive strengths of mortar with stone ash is increases from normal mortar in variations 5%, 10% and 15% with the percentages of 4.66%, 3.41% and 2.38% respectively, while in the variation of 20% and 25%  is decreases. Compressive strength of mortar with mixture bagasse ash and stone ash reduce from normal mortar with a decrease of 0.08%, 1.04%, 5.67%, 8.06% dan 15.12% respectively.